Photoelectric response of localized states in silica glass - Trukhin, Anatoly N. (Elsevier B.V., 2019)
The photoelectric response of pure silica glasses excited by excimer lasers has been studied. The samples were made under various conditions. Photoelectric polarization of samples due to the Dember effect has been registered. The signal was recorded under the conditions of a space charge limited current. The space charge resulting from the capture of electrons and holes creates a static electric field that prevents diffusion of released charge carriers. The current registration in the external circuit stops, despite the continuation of photoexcitation. This effect was used as a fact of measuring the photocurrent in the sample volume instead of the parasitic current that is not associated with the sample. The screen has been chosen to prevent the influence of a spurious signal. It has been found that charge carriers are released when excited in the spectral absorption range of localized states of silica. Based on the Dember effect, the sign of the photoelectric response shows the type of charge carriers - an electron or a hole is mobile. Thus, a sample containing aluminum without alkali ions gives a negative signal, which indicates the diffusion of electrons at 290 K, since aluminum is an effective hole trap. An oxygen-deficient sample at 290 K provides a positive signal indicating the diffusion of holes, because the center of oxygen deficiency is an effective electron trap. This sample at 100 K provides a negative signal due to the effective self-trapping of holes.
This work was supported by the Latvian Science Council Grant No lzp-2018/1-0289.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Silica; Localized states; Photoconductivity; Dember effect; Space charge limited current